Testimony and its Mediations in Life Writing. Issue 3 (3rd July 2022) - Woods, Roger
ABSTRACT: The following analysis looks at current discussions surrounding testimony in the form of life writing. In particular it looks at how competing theories of mediation fare when applied to concrete examples of testimony as it is shaped by its authors and re-presented by its users, and it examines how the concepts of dominant narratives and the subjective experience impact on individual testimony's form and status. Dominant narratives are demonstrably present in individual testimony, but their presence may be detected in authors' resistance to them. Doubts about the referential value of testimony have encouraged one line of research to relocate its significance in the emotional sphere, but this relocation leaves it with little explanatory value. Against this background I examine three critical approaches to testimony that strike a balance between author agency and critical evaluation: relationality, innertextuality and intertextuality. Rather than deploying testimony as a series of 'soundbites' to prove a pre-existing theory, these approaches reveal the internal dynamics of testimony and its particular affordances.